2021
DOI: 10.3390/su13137473
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis and Management of Construction and Operations in Offshore Wind Power Project

Abstract: Many countries have increased the use of renewable energy and strongly promoted offshore wind power (OWP). However, OWP in Asia is in the preliminary stage of development, for which no precedents exist. The literature on wind energy generation has mostly investigated the causes of onshore wind turbine accidents and risk prevention, and more work on the risks associated with domestic OWP is required for energy market development. According to statistics on international wind power accidents, most offshore accid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…This paper summarizes the latest research results of several domestic and foreign scholars on the risks of offshore wind power projects. About the risks of offshore wind power, except for the different classification standards, it can be seen that the general direction of the overall risk is consistent (Gatzert and Kosub 2016;Chou et al 2021;Sovacool et al 2017), as shown in Table 2. However, in terms of the identification of primary risk factors for offshore wind power PPP projects, the existing risk assessment index system for offshore wind power PPP projects is not an idea and needs to be modified.…”
supporting
confidence: 56%
“…This paper summarizes the latest research results of several domestic and foreign scholars on the risks of offshore wind power projects. About the risks of offshore wind power, except for the different classification standards, it can be seen that the general direction of the overall risk is consistent (Gatzert and Kosub 2016;Chou et al 2021;Sovacool et al 2017), as shown in Table 2. However, in terms of the identification of primary risk factors for offshore wind power PPP projects, the existing risk assessment index system for offshore wind power PPP projects is not an idea and needs to be modified.…”
supporting
confidence: 56%
“…The general methodology enabling the development of risk register has been suggested by [32], on the other hand, models designed directly for specific types of buildings are also available, e.g. for wastewater treatment plants [33] or offshore wind power facilities [34].…”
Section: Pmic: Going Beyond Its Traditional Capabilitiesmentioning
confidence: 99%
“…Xuemin Zhang et al [12] identified hidden risks in the design, manufacturing, transportation, construction, operation, and maintenance phases of wind power industry products from the perspective of the industry chain and introduced corresponding risk management insurance strategies. Jui-Sheng Chou et al [13] identified risk factors in the construction and operation of offshore wind farms in Taiwan. The risk rankings and preventive measures can serve as references for relevant industry personnel in island cities and nearby Asian countries to reduce risk in the management of OWP projects.…”
Section: Introductionmentioning
confidence: 99%